FORMATION OF DIGITAL COMPETENCE IN UNIVERSITY STUDENTS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Mallaboyev Nosirjon Murodullayevich, docent; Qosimova Zulfiyaxon Mo’minovna, teacher (Western European Studies, 2024)
This article discusses the ways and content of improving students’ digital competencies in the digital technology environment, as well as effective tools. How to equip teachers with new digital competencies is described using the example of global pedagogy. Digitalization and the introduction of computerization affects all spheres of life and society. The importance of digital technologies in higher education and the requirements for their rational and effective use are presented
Keywords: digital technologies; digital competence; foreign experience